ANALISIS FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAANPROPERTY DAN REAL ESTATEYANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayu Suriayu; Renil Septiano (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Capital is a very important factor for a company to fund its business activities and maintain the sustainability of the company's development. Capital structure is a company that is expressed in the form of an obligation to make the right decisions and use the best way to achieve company goals. This study aims to analyze the Effect of Sales Stability and Asset Structure on Capital Structure in property and real estate companies listed on the Indonesia Stock Exchange in 2016-2021. The population used in this study are property and real estate companies listed on the Indonesia Stock Exchange, totaling 45 companies. In this study the technique used to determine the sample is purposive sampling technique. The samples used in this study were 9 companies